2011
DOI: 10.1017/s0033291711001905
|View full text |Cite
|
Sign up to set email alerts
|

Depression symptom dimensions as predictors of antidepressant treatment outcome: replicable evidence for interest-activity symptoms

Abstract: Background Symptom dimensions have not yet been comprehensively tested as predictors of the substantial heterogeneity in outcomes of antidepressant treatment in major depressive disorder. Method We tested nine symptom dimensions derived from a previously published factor analysis of depression rating scales as predictors of outcome in 811 adults with moderate to severe depression treated with flexibly dosed escitalopram or nortriptyline in Genome-based Therapeutic Drugs for Depression (GENDEP). The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
262
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(277 citation statements)
references
References 57 publications
11
262
2
2
Order By: Relevance
“…Indecisiveness and the other interest-activity depressive symptoms (including low interest, reduced activity, and lack of enjoyment) were proposed as predictors of poor treatment outcomes to escitalopram and nortriptyline in 811 adults with moderate to severe depression in the study Genome-based Therapeutic Drugs for Depression (GENDEP) (Ulher et al 2009). Similar findings have been reported in 3,637 MDD adults treated with citalopram in Sequenced Treatment Alternatives to Relieve Depression (STAR*D) (Ulher et al 2012). In addition, indecisiveness, guilt, ideas of reference, depressed mood, insomnia and other symptom dimension were proposed as predictors of depression that is resistant to escitalopram and nortriptyline in 793 adults with MDD (Iniesta et al 2016).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Indecisiveness and the other interest-activity depressive symptoms (including low interest, reduced activity, and lack of enjoyment) were proposed as predictors of poor treatment outcomes to escitalopram and nortriptyline in 811 adults with moderate to severe depression in the study Genome-based Therapeutic Drugs for Depression (GENDEP) (Ulher et al 2009). Similar findings have been reported in 3,637 MDD adults treated with citalopram in Sequenced Treatment Alternatives to Relieve Depression (STAR*D) (Ulher et al 2012). In addition, indecisiveness, guilt, ideas of reference, depressed mood, insomnia and other symptom dimension were proposed as predictors of depression that is resistant to escitalopram and nortriptyline in 793 adults with MDD (Iniesta et al 2016).…”
Section: Discussionsupporting
confidence: 84%
“…It has been reported that cognitive dysfunction is already present at an early stage of depressive disorders and is maintained even in remission (Woo et al 2016). Impaired concentration or indecisiveness has been proposed as a predictor of poor antidepressant treatment outcome (Ulher et al 2012). Regarding psychiatric taxonomy, impaired concentration has been a symptom of depression, although it is also a criterion for other disorders (Zimmerman et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The enthusiasm for biomarker identification has overshadowed a long history of efforts to direct prescribing on the basis of clinical observations, i.e., by identifying patient subgroups on the basis of clinical symptomatology or comorbidity (34 ). For example, anxiety, psychotic-like symptoms, and other sets of depressive symptoms have been associated with poorer treatment response (35)(36)(37). Two relatively recent developments might make this strategy more practical: the emergence of larger clinical data sets, including those drawn from large effectiveness studies, electronic health records (38 ), and patient self-report in direct-to-consumer genomics testing (39 ), as well as the application of newer machine learning tools.…”
Section: Emerging Areas Of Investigationmentioning
confidence: 99%
“…Anhedonia, defined as a loss of interest or pleasure in previously enjoyable activities, is linked with disrupted transmission in the mesocorticolimbic dopamine system and is clinically important because it predicts poor response to standard antidepressant treatment (McMakin et al, 2012;Uher et al, 2012). Although there is currently no effective treatment specifically for anhedonia, suppression of habenula neuron firing has been shown to resolve depressive-like behaviour in rats (Li et al, 2011) and was reported to treat symptoms in a treatment-refractory patient through deep-brain stimulation (DBS) (Sartorius et al, 2010), suggesting a potential avenue for the development of novel therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%